CD14/TLR4 priming potentially recalibrates and exerts anti-tumor efficacy in tumor associated macrophages in a mouse model of pancreatic carcinoma - Prakash, Hridayesh; Schmitz-Winnenthal, Friedrich Hubertus (Scientific reports, 2016)
Pancreatic cancer is the fourth major cause of cancer related deaths in the world and 5 year survival is below 5%. Among various tumor directed therapies, stimulation of Toll-like receptors (TLR) has shown promising effects in various tumor models. However, pancreatic cancer cells frequently express these receptors themselves and their stimulation (TLR 2 and/or 4 particularly) within tumor microenvironment is known to potentially enhance tumor cell proliferation and cancer progression. Consistent stimulation of tumor associated macrophages (TAMs), in particular with tumor derived TLR ligand within the tumor microenvironment promotes cancer related inflammation, which is sterile, non-immunogenic and carcinogenic in nature. In view of this, recalibrating of TAM has the potential to induce immunogenic inflammation. Consistent with this, we provide experimental evidence for the first time in this study that priming of TAMs with TLR4 ligend (LPS) alone or in combination with IFN-γ not only recalibrates pancreatic tumor cells induced M2 polarization, but also confers anti-tumor potential in TAMs. Most interestingly, reduced tumor growth in macrophage depleted animals suggests that macrophage directed approaches are important for the management of pancreatic tumors.
Gesehen am 21.03.2018